An assessment of the records and the records management practices of the University of the Philippines Computer Center - Bernardo, Jose Paolo P. (School of Library and Information Studies, University of the Philippines Diliman, 2018)
This is study is an assessment of the records and the records management practices of the University of the Philippines Diliman Computer Center (UCC). It determined and enumerated the records and records management practices of UCC, assess them and documented any problems were encountered while handling them. A guided answering of the survey questionnaire and an inventory of the records were conducted from March 20 May 7, 2018 at the UCC office. The persons primarily in charge of the records were the respondents of this study.